Dietary Sodium Intake: Knowledge, Attitudes and Practices in Shandong Province, China, 2011 - Zhang, Juan (Public Library of Science, 2013)
OBJECTIVE: To investigate the knowledge, attitudes and practices (KAP) for dietary sodium intake among adult residents of Shandong Province, China METHODS: In 2011, we conducted a cross sectional survey among a representative sample of 15,350 adults aged 18 to 69 years using a standardized questionnaire to assess their KAP for sodium. Variation in the KAPs by gender, and residence location were compared using the Chi-square tests. Predictors for the ‘intention to’ and ‘currently taking action to’ reduce sodium intake were determined by multivariate logistic regression with adjustment for confounding factors. RESULTS: KAPs for dietary sodium intake among urban residents was generally more favorable than among rural residents. Women were likely to have more favorable KAPs than men. About four fifth of subjects reported that they favored a low sodium diets. However, 31% reported that consumption of less sodium results in less physical strength. Overall, 70% indicated their intention to reduce sodium intake, although only 39 % reported that they had taken action to reduce sodium. Multiple logistic regression analyses indicated that favorable actions to dietary sodium reduction were more likely to occur among those who were aware of the link between sodium and hypertension, and less likely among those who had unfavorable attitudes towards dietary sodium reduction. CONCLUSION: Increasing knowledge levels about the benefits of sodium reduction will be a key success factor for effective sodium reduction initiatives and is linked to favorable behavioral change. Emphasis should be placed on the rural area.